Intoxication by rodenticides (raticides) with superwafarins: Anticoagulant effect may be highly prolonged - Riveros-Anglas, Marisa (2021)
19-year-old young man who made a suicide attempt in february 2019, ingesting 04 bags of rat poison “Klerat”. Taken to Emergency in the city of Tarapoto (San Martín Region); they perform gastric lavage; Receive 2 doses of Phytomenadione and send it to your home. At 11 days post-intoxication, he presents musculoskeletal pain, reddish urine, bleeding from the gums, epistaxis, bruising, increased gingivorrhagia and a feeling of fainting; He is taken to the Yurimaguas Hospital. Laboratory tests find: INR: 9.7 and changes in Prothrombin Time (PT): 45 and Activated Partial Thromboplastin Time (APTT): 60. He receives treatment with Phytomenadione and Tranexamic Acid. For the persistence of scarce gingivorrhagia and coagulation disorders, the reference is made to the Dos de Mayo National Hospital in the city of Lima. Where found: INR: 11.5, TP: 120 sec. APTT: 86.5, Hb: 12.2 Leukocytes: 10,090 Platelets: 320,000, Urine: red blood cells 5xc. Leukocytes: 0-1 x c. Liver profile: Normal, Lipid profile: Normal, Rx. Chest. Normal, D-Dimer: 0.14. Autoimmunity tests are performed, finding the Lupus Anticoagulant: Positive, with the rest being negative. Tto was given. with fresh frozen plasma, cryoprecipitate and phytomenadione. The urine test on CICOTOX found POSITIVE hydroxycoumarin metabolites. He was hospitalized for 2 months, stabilization is achieved in the coagulation profile and INR, dependent on Tto. with Phytomenadione. CICOTOX urine control was negative at 2 months. Control of the Lupus anticoagulant at 3 months was Positive; at 6 months he gave a Negative. He had to continue with Tto. of Phytomenadione for 10 more months (Dec. 2019), until achieving total stabilization of the coagulation profile and INR. To discharge you.